Analysis of tax law on income tax for construction services business - Victoria Pasari Putri (Central Research Institute for Agriculture (CeRIA), 2023)
This study aims to analyze the implementation of the provisions Article 4 paragraph (2) letter d of the Income Tax Law and Article 23 paragraph (1) letter c number 2 of the Income Tax Law regarding the withholding of income tax for construction services businesses and the application of deductions to Article 23 paragraph (1) letter c number 2 of the Income Tax Law regarding business income tax deductions construction service? This research was conducted at CV. Mandala Putra and Office Services, counseling, and tax consulting in North Toraja Regency. The method used in this study was field research where data collection was carried out by interviewing and taking into account the books and applicable laws and regulations. The data obtained were then analyzed qualitatively and presented descriptively. The results of this study indicate: 1). Implementation of the provisions of Article 4 paragraph (2) letter d and Article 23 paragraph (1) letter c number 2 of the Income Tax Law related to the withholding of income tax for construction services businesses, namely the existence of a qualification requirement intended in the form of a business entity certificate issued by a construction service development agency for tax imposition which are final due to certificates and non-certified business entities are subject to non-final tax 2). In applying the tax of Article 23 paragraph (1) letter c number 2 in the construction service business, it is carried out by the cutting party by first making a billing ID, then paying it through a Perception Bank that has been approved by the Ministry of Finance. The payment due date is the 10th, one month after the month the income tax is due. After that Reporting is done by the cutting party by filling out Periodic Income Tax Return Article 23, then you can report it through the online tax report feature or free efiling on Online Tax. The reporting due date is the 20th, a month after the month the income tax is due.